Clinical and histopathological features of asymptomatic persistent microscopic hematuria in children - (:unkn) unknown (My University, 2016)
0

Background/aim: We analyzed the clinical and pathological features and prognosis of 106 children with persistent asymptomatic microscopic hematuria (PAMH) with or without mild proteinuria. Materials and methods: This was a retrospective study of 106 children who were referred to our clinics from 2000 to 2013 for evaluation of PAMH. Results: Among the 106 patients, 69 (65%) were female and 37 (35%) were male. The patients were divided into two groups: 101 patients with isolated microscopic hematuria (IMH) and 5 patients with asymptomatic microscopic hematuria and mild proteinuria (AMHP). Renal biopsy was performed in all 5 children with AHMP: 2 patients had hereditary nephropathy and 2 patients had focal segmental glomerulosclerosis (FSGS). One biopsy specimen revealed nonspecific findings. Renal biopsy was performed in 9 children with IMH: 4 patients had hereditary nephropathy and 5 patients had nonspecific findings. None of the patients received any specific treatment prior to renal biopsy. During the follow-up period, none of the patients developed impaired renal function. Among all the children, only one patient with AMHP developed hypertension and 2 patients with IMH developed proteinuria. Conclusion: Long-term follow-up must be done carefully for isolated microscopic hematuria and renal biopsy should be performed in selected cases.
Keywords: Cerrahi